428 Interim analysis of Phase 2 results for cemiplimab in patients with metastatic basal cell carcinoma (mBCC) who progressed on or are intolerant to hedgehog inhibitors (HHIs). (10th December 2020) - Lewis, Karl; Peris, Ketty; Sekulic, Aleksandar; Stratigos, Alexander; Dunn, Lara; Eroglu, Zeynep; Chang, Anne Lynn; Migden, Michael; Li, Siyu; Mohan, Kosalai; Coates, Ebony; Okoye, Emmanuel; et al.
Abstract : Background: HHIs, vismodegib and sonidegib, are approved for treatment of patients with mBCC or locally advanced BCC who are not candidates for surgery or radiation. There is no approved option for patients who progress on or are intolerant to HHIs. Cemiplimab is an anti-programmed cell death-1 monoclonal antibody approved for treatment of patients with metastatic cutaneous squamous cell carcinoma (CSCC) or locally advanced CSCC who are not candidates for curative surgery or curative radiation. Here we present the prespecified interim analysis of the mBCC cohort from the pivotal Phase 2, non-randomized, multi-center study of cemiplimab in patients with advanced BCC who discontinued HHI therapy due to disease progression, intolerance, or no better than stable disease after 9 months (NCT03132636 ). Methods: Patients with mBCC (nodal and/or distant) received cemiplimab 350 mg intravenously every 3 weeks; interim analysis included patients with the opportunity to be followed for approximately 57 weeks. The primary endpoint was objective response rate (ORR) per independent central review (ICR). Secondary objectives included assessment of safety and tolerability, estimation of duration of response (DOR), progression-free survival (PFS), and overall survival (OS). Results: In this interim efficacy analysis of 28 patients, 82.1% were males and median age was 65.5 years (range 38−90). Six patients had a partial response, per ICR, for an ORR of 21.4% (95% CI, 8.3, 41.0). ORR per investigator assessment was 28.6% (95% CI, 13.2, 48.7). Among responders, observed DOR was 9−23 months. Median time to response per ICR was 3.2 months (range, 2.1−10.5). Median Kaplan–Meier (KM) estimation of PFS was 8.3 months. Median DOR had not been reached and median KM estimation of OS was 25.7 months. All six responses had observed durations of at least 8 months. The disease control rate was 67.9% (95% CI, 47.6, 84.1).The most common treatment emergent adverse events (TEAEs) regardless of attribution were fatigue (50.0%), diarrhea (35.7%), pruritus (25.0%), and constipation (25.0%). Hypertension (n=2) was the only Grade ≥3 TEAE regardless of attribution occurring in ≥2 patients. TEAEs leading to death occurred in one (3.6%) patient who died from staphylococcal pneumonia, considered unrelated to study treatment. Conclusions: This interim analysis demonstrates that cemiplimab is the first agent to provide clinically meaningful anti-tumor activity, including durable responses, in patients with mBCC after progression or intolerance on HHI therapy. Acknowledgements: Editorial acknowledgment: Medical writing support was provided by Cindi Hoover, PhD of Prime, Knutsford, UK, funded by Regeneron Pharmaceuticals, Inc. and Sanofi. Ethics Approval: The study protocols and all amendments were approved by the institutional review board at each participating study site. The study was conducted in accordance with the principles of the Declaration of Helsinki and with Good Clinical Practice guidelines as defined by the International Conference on Harmonization. All patients provided written informed consent before enrollment.